2018
DOI: 10.4236/ijcm.2018.94024
|View full text |Cite
|
Sign up to set email alerts
|

Injury Pattern among Road Traffic Accidents’ Victims in Najran City, Saudi Arabia

Abstract: Traffic accidents constitute the substantial cause of disability and mortality in the young Saudi individuals reaching horrible figures. The aim of this study was to review and identify the pattern of injury among road traffic accident (RTA) victims as well as the peak time of accidents and their implications. This retrospective hospital-based cross-sectional study was carried out in the period between April 2016 to March 2017 in King Khalid Hospital, Maternity and Children Hospital and Najran General Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
4
7
0
1
Order By: Relevance
“…About 33% of crash victims suffered head and/or neck injuries. This result was in accordance with those of other regional and international studies [ 28 , 29 ]. When victims were asked about the reason for the current crash, they reported that excessive speed or use of a mobile phone was the major reason.…”
Section: Discussionsupporting
confidence: 94%
“…About 33% of crash victims suffered head and/or neck injuries. This result was in accordance with those of other regional and international studies [ 28 , 29 ]. When victims were asked about the reason for the current crash, they reported that excessive speed or use of a mobile phone was the major reason.…”
Section: Discussionsupporting
confidence: 94%
“…These results were in partial agreement to Shamim (2017) study in India who revealed that the most common RTA injuries were at lower extremities, followed by the head and neck, multiple injuries, upper extremities, abdomen, pelvis, and perineum, and finally chest. Al-Zamanan et al (2018) in Saudi Arabia revealed that the most common RTA injuries were head injuries, followed by lower limb and spinal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to a previous study conducted in the Aseer region where the highest incidence of RTAs occurred during daytime (59.9%) [ 24 ]. On the contrary another study concerning timing showed that 58% of the RTAs happened during the evening (6:00 p.m.-9:00 p.m.) and 20% happened in the morning [ 25 ].…”
Section: Discussionmentioning
confidence: 99%